Quantitative Assessment of Temporal Changes in Subaqueous Hydrothermal Activity in Active Crater Lakes During Unrest Based on a Time-Series of Lake Water Chemistry - Terada, Akihiko; Yaguchi, Muga; Ohba, Takeshi (Frontiers in Earth Science, 2022)
Regular sampling of lake water has been performed at many volcanoes to assess volcanic activity. However, it is not clear whether the absolute concentrations or rate of changes in concentrations are more suitable for such assessments. In this study, we show that temporal changes in concentrations of an element in lake water are described by a simple deferential equation, assuming changes in volume and chemical processes are negligible. The time constants have a wide range of between 20–1,000 day for the studied volcanoes in Japan, meaning it takes a long time to assess volcanic activity based on the absolute concentration of an element. In order to assess the volcanic activity in a shorter time period, based on a time-series of lake elemental concentration data, we developed a numerical model to calculate temporal changes in the steady state concentration, which is proportional to the elemental concentrations in subaqueous fumaroles. We applied our method to Yugama crater lake at Kusatsu–Shirane volcano, Japan, and quantitatively evaluated temporal changes in subaqueous fumarolic activity from 1964–2020. As a result, we detected changes in Cl concentrations in subaqueous fumaroles that were associated with volcanic unrest. Comparing with temporal changes of CO2 emitting from nearby fumaroles, we propose that some of the CO2 was derived from a deep magma reservoir, whereas Cl was supplied from the crystallizing magma. Phreatic eruptions or significant turbulent events at the lake water surface occurred 1–5 years after the onset of the decrease in the steady state Cl concentration. The sealing of the fluid pathway to the lake from the hydrothermal reservoir or fluid circulation changes associated with the self-sealed zone surrounding the crystallizing magma are thought to have triggered these events. The future concentration in the lake water can be predicted from the most recent steady state concentrations. Comparing predicted concentration curve with the concentration obtained from lake water samples, it is possible to assess whether the concentration in the subaqueous fumaroles has increased/decreased or remained constant.